2024
DOI: 10.1093/bjs/znae075
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence-guided hemithyroidectomy in a low-volume thyroid institution with no experience in parathyroid surgery: randomized clinical trial

Ali Abood,
Lars Rolighed,
Therese Ovesen
et al.

Abstract: Background Recent studies suggest that low-volume surgeons with no experience in parathyroid surgery are at increased risk of causing parathyroid gland damage during thyroid surgery. The aim of this RCT was to evaluate the impact of using autofluorescence in hemithyroidectomy on parathyroid gland identification and preservation in a low-volume institution with no experience in parathyroid surgery. Methods Patients referred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Previous studies have shown NIRAF’s superiority over naked eye visualization during surgery ( 16 ). This study, consistent with recent research in other low-volume institutions ( 17 , 18 ), offers valuable insights into the impacts that autofluorescence guidance may have on surgical outcomes, particularly for less experienced surgeons.…”
supporting
confidence: 84%
“…Previous studies have shown NIRAF’s superiority over naked eye visualization during surgery ( 16 ). This study, consistent with recent research in other low-volume institutions ( 17 , 18 ), offers valuable insights into the impacts that autofluorescence guidance may have on surgical outcomes, particularly for less experienced surgeons.…”
supporting
confidence: 84%